Impact of aquaculture on water quality and heavy metals in the water and sediment of Selang Sibu river - Nuraminah, Jaafar (Universiti Malaysia Sarawak (UNIMAS), 2011)
Aquaculture is the farming of aquatic plants and animals. Aquatic farming such as shrimp farming in the tributary, Selang Sibu River, generates income and provides food. The objectives of this study were to evaluate the impacts of aquaculture on the water quality and sediment of Selang Sibu River. Samplings were conducted in six stations. Results indicated that the total phosphorus (TP), and ammonia-nitrogen (NH3-N) in water were recorded high in shrimp farm discharge due to shrimp farm effluent. pH of water and sediment samples were in alkaline conditions and fall in Class I according to INWQS. Total organic carbon (TOC) values were in decreasing order of S2>S1>S3>S4>S5>S6. In sediment quality, the TP concentration was high at shrimp farm discharge. The textures of the sediment among the stations were sandy clay and sandy clay loam. Concentrations of Iron (Fe) were higher at station S1 near shrimp farm discharge in water and sediment samples. Concentrations of Cadmium (Cd) were under detection limit for water and sediment samples.